Speech Act Classification and Request Strategy in “Tall Girl” Movie Directed by Nzingha Stewart - Ary Iswanto Wibowo; Gilang Cempaka (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The research is aimed to find out the speech act classification and types of request strategy from a dialogue of the characters in Tall Girl movie. The method of this study is descriptive qualitative analysis. Data is taken out of all dialogues of the characters and is observed by using theories. In this analysis, the writers found the speech Act Classification and Types of Request Strategy in the Speech Act. The speech act is classified in declaration, representatives, directives, commissives, and expressive. Directives served the dominant form among the five types of illocutionary act mostly expressed their utterance. And as request strategy is typed in mood derivable, explicit performative, hedged performative, locution derivable, want statement, suggestive formula and preparatory. Mood derivable served the dominant form among the other types to deliver their willingness.